2011
DOI: 10.1007/s10682-011-9520-8
|View full text |Cite
|
Sign up to set email alerts
|

Does life in unstable environments favour facultative selfing? A case study in the freshwater snail Drepanotrema depressissimum (Basommatophora: Planorbidae)

Abstract: One of the main advantages of self-fertilization is to provide reproductive assurance when pollen or mates are scarce. In plants, partial or facultative selfing limits the risk of pollination failure. In preferentially outcrossing species, this may result in mixedmating. In hermaphroditic animals, recent studies suggest that mixed mating might be much rarer than in plants. However more studies are required to substantiate this claim, especially focusing on species whose lifestyle entails a high potential benef… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
7
0

Year Published

2012
2012
2024
2024

Publication Types

Select...
6
2

Relationship

2
6

Authors

Journals

citations
Cited by 14 publications
(9 citation statements)
references
References 44 publications
2
7
0
Order By: Relevance
“…; Lamy et al . ). At each site, eight to 32 snails (mean = 21.77 ± 7.78) were collected corresponding to a total of 1633 individuals (902 and 731 in 32 and 43 sites in D. depressissimum and A. marmorata, respectively; previous rarefaction analysis suggested that sampling ten to 15 individuals per population for both species allows to capture difference in GD).…”
Section: Methodsmentioning
confidence: 97%
See 2 more Smart Citations
“…; Lamy et al . ). At each site, eight to 32 snails (mean = 21.77 ± 7.78) were collected corresponding to a total of 1633 individuals (902 and 731 in 32 and 43 sites in D. depressissimum and A. marmorata, respectively; previous rarefaction analysis suggested that sampling ten to 15 individuals per population for both species allows to capture difference in GD).…”
Section: Methodsmentioning
confidence: 97%
“…2000) but also a few small gullies (which consist of succession of ponds occasionally connected by water flow) and swamp grasslands connected to mangroves (Bruyere & Questel ; Pointier & David ; Lamy et al . ,b, ). Some of these sites are permanent, but many ponds completely dry out, either yearly or more irregularly, during the dry season (i.e.…”
Section: Methodsmentioning
confidence: 97%
See 1 more Smart Citation
“…These observations suggest M. hystrix may in fact frequently encounter environmental conditions of high mate availability and intense sperm competition, coupled with an ability to deal with periods of low mate availability through the delayed selfing behaviour we demonstrate in this study (c.f. for example Lamy et al, 2012).…”
Section: Macrostomum Hystrix Exhibits Delayed Selfingmentioning
confidence: 99%
“…The method assumes an infinitely large source population providing immigrants to the focal population in which N e and m are estimated. Generation time was fixed at two months (based on laboratory cultures, Lamy et al. 2012), and the maximum N e was set at 4000.…”
mentioning
confidence: 99%